Rapamycin attenuates the progression of tau pathology in P301S tau transgenic mice. - Sefika Ozcelik; Graham Fraser; Perrine Castets; Véronique Schaeffer; Zhiva Skachokova; Karin Breu; Florence Clavaguera; Michael Sinnreich; Ludwig Kappos; Michel Goedert; Markus Tolnay; David Theo Winkler (PLoS ONE, 2013)
Altered autophagy contributes to the pathogenesis of Alzheimer's disease and other tauopathies, for which curative treatment options are still lacking. We have recently shown that trehalose reduces tau pathology in a tauopathy mouse model by stimulation of autophagy. Here, we studied the effect of the autophagy inducing drug rapamycin on the progression of tau pathology in P301S mutant tau transgenic mice. Rapamycin treatment resulted in a significant reduction in cortical tau tangles, less tau hyperphosphorylation, and lowered levels of insoluble tau in the forebrain. The favourable effect of rapamycin on tau pathology was paralleled by a qualitative reduction in astrogliosis. These effects were visible with early preventive or late treatment. We further noted an accumulation of the autophagy associated proteins p62 and LC3 in aged tangle bearing P301S mice that was lowered upon rapamycin treatment. Thus, rapamycin treatment defers the progression of tau pathology in a tauopathy animal model and autophagy stimulation may constitute a therapeutic approach for patients suffering from tauopathies.